2014
DOI: 10.1002/job.1923
|View full text |Cite
|
Sign up to set email alerts
|

Social context: Key to understanding culture's effects on creativity

Abstract: This paper proposes that the social context moderates the effect of culture on creativity by drawing on the constructivist dynamic approach. We assess creativity by the level of fluency, originality, and elaboration on the usefulness and appropriateness of ideas in three contexts: working under a supervisor, in a group, and alone. We hypothesized that in high power distance cultures, working under a supervisor inhibits creativity, whereas in individualistic cultures, the presence of peers attenuates creativity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 86 publications
(146 reference statements)
5
55
0
3
Order By: Relevance
“…We also show that face logic endorsement predicts creativity above and beyond individualism and collectivism values. Second, we advance recent theories that differentiate between the processes and values associated with the novelty and appropriateness dimensions of creativity (Berg, ; Mueller, Melwani, & Goncalo, ; Nouri et al, ; Paletz & Schunn, ). We show that face logic mainly hinders idea novelty and fluency, but not the appropriateness of generated ideas.…”
Section: Face Cultural Logic and Creativitymentioning
confidence: 62%
See 2 more Smart Citations
“…We also show that face logic endorsement predicts creativity above and beyond individualism and collectivism values. Second, we advance recent theories that differentiate between the processes and values associated with the novelty and appropriateness dimensions of creativity (Berg, ; Mueller, Melwani, & Goncalo, ; Nouri et al, ; Paletz & Schunn, ). We show that face logic mainly hinders idea novelty and fluency, but not the appropriateness of generated ideas.…”
Section: Face Cultural Logic and Creativitymentioning
confidence: 62%
“…and/or a subordinate ( Fs < 3.16, n.s. ), thus ruling out the possibility that differences in the presence of these figures in the situation affected creativity (Nouri et al, ; Zhou & Su, ). These content analyses lend additional support to the effectiveness and equivalence of our social‐image affirmation manipulation in these three cultures.…”
Section: Study 2—resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The semi-structured interviews reveal a wealth of different domains and categories related to creativity, and highlight the need for a holistic, action oriented, and system-oriented approach when studying creativity. The findings also broaden a narrow cognitive view on creativity, highlighting also the role of motivational and socio-cultural factors during the creative process (for the role of societal context in creativity see also Nouri et al 2014).…”
Section: Discussionmentioning
confidence: 54%
“…Cultural support for integrating paradoxes increases the likelihood that individuals will use paradoxical frames, but is not a specific claim about how individuals will interpret specific conditions. The effect of culture hinges on the situational conditions (Nouri et al, 2015). Conditions create opportunities for using paradoxical frames, and specific, predictable conditions create opportunities that can be identified through analysis, as the current studies demonstrated.…”
Section: Discussionmentioning
confidence: 88%